Discrimination of Pakistani Fountain Pen Inks by Gas Chromatography-Mass Spectrometry (GC-MS). (30th March 2022) - Sharif, Mehwish; Jalees, Muhammad Irfan; Ali Shah Tirmazi, Syed Azhar; Athar, Muhammad Makshoof; Durrani, Arjumand Iqbal; Batool, Madeeha
Abstract : In developing countries, the chances of fraud in written documents are comparatively high. Therefore, comparison of fountain pen inks is especially imperative in examination of forensic questioned documents. We have investigated the use of the gas chromatography-mass spectrometry technique in profiling and discrimination of fountain pen ink used in Pakistan for forensic purpose. The main purpose of this study was to discriminate different Pakistani fountain pen inks. The datum for Pakistani inks of fountain pen is not obtainable. In this research study, blue, black, and green colors fountain pen inks commercially used in Pakistan have been extracted from paper using micropunch and then investigated using the gas chromatography-mass spectrometry technique. Gas chromatography-mass spectrometry (GC-MS) was used to differentiate various brands of different colors of fountain pen inks based on their chemical composition. Molecular ion peaks for different components were obtained, and components were identified on the basis of detected ions. Results have been calculated and compared in terms of discriminating power (D.P.). The D.P. for blue, black, and green inks of fountain pen was 1.0 by using the gas chromatography-mass spectrometry technique.